Towards Environmental Innovation Systems - Weber, K. Matthias.; Weber, K. Matthias.; Hemmelskamp, Jens.; Hemmelskamp, Jens. (Springer Berlin Heidelberg : Imprint: Springer, 2005)
The book brings together research communities from different disciplines and countries, and offers an exchange about theoretical frameworks and practical experiences to guide research and policy "towards environmental innovation systems". The contributions selected explore new directions of research at the borderline between two established research traditions: systems of innovation and environmental innovations. For this purpose, the book draws on recent conceptual and empirical insights as well as on policy-oriented analyses. It is structured according to the four main areas of interest with respect to environmental innovation systems: conceptual foundations, empirical experiences, strategic approaches, and experiences with policy instruments.